Cytotoxic CD4 T cells in the mucosa and in cancer - Venkatesh, Hrishi; Tracy, Sean I.; Farrar, Michael A. (Frontiers in Immunology, 2023)
CD4 T cells were initially described as helper cells that promote either the cellular immune response (Th1 cells) or the humoral immune response (Th2 cells). Since then, a plethora of functionally distinct helper and regulatory CD4 T cell subsets have been described. CD4 T cells with cytotoxic function were first described in the setting of viral infections and autoimmunity, and more recently in cancer and gut dysbiosis. Regulatory CD4 T cell subsets such as Tregs and T-regulatory type 1 (Tr1) cells have also been shown to have cytotoxic potential. Indeed, Tr1 cells have been shown to be important for maintenance of stem cell niches in the bone marrow and the gut. This review will provide an overview of cytotoxic CD4 T cell development, and discuss the role of inflammatory and Tr1-like cytotoxic CD4 T cells in maintenance of intestinal stem cells and in anti-cancer immune responses.